Penggunaan Media Flash Card Dalam Meningkatkan Kemampuan Membaca Permulaan Pada Anak Tunagrahita Ringan Kelas Dasar III di SLB Finjili Pulau Lembeh - Samsul Samsul (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine whether the use of flash card media can improve initial reading, namely in distinguishing letters that have a sound or shape that is almost similar to the letters “b” with “d”, the letters “m” with “n”, and the letter “j” with “g” in the form of words for mild mentally retarded children in elementary classs III SLB Finjili Lembeh Island, for example in the word “finger”, “table”, “bench”, “ball”, and “book”. Examples in the word “finger” students experience difficulties when reading letters “j” which often becomes “g” so when reading it becomes “gari”. The method used in this research single subject experiment method or Single Subject Research (SSR). The research used is the A-B-A-B design, which consists of baseline-1, intervention-1, baseline-2, intervention-2 the research subjects were mild mental retardation students in elementary class III at SLB Finjili Lembeh Island, namely JM subjects. Data collection was carried out using observation, interviews, and documentation. Data analysis in the form of analysis under conditions and analysis between conditions. The results showed that the use of flash card media can inprove initial reading, namely in distinguishing letters that have a sound or shape that is almost similir to the letters “b” with “d” letters “m” with “n”, and the letters “j” with “g” in the form of words for children with mild mental retardation elementary class III SLB Finjili Lembeh Island, for example in the word “finger”, “tables”, “benches”, “balls” and books. Viewed in terms of frequency in distinguishing letters that have a sound or shape that is almost similar in word form . It is shown with data that overlaps 20%. Based on the resultsof the study, it can be concluded that the use of flash card media can improve distinguishing letters that have a sound or shape that is almost similar in word form to mild mentally retarded children in elementary class III SLB Finjili Lembeh Island.